The Preservative Effect of the Black Rice's Cold, Hot and Ultrasonic Ethanol Extracts on the Storage Quality of Beef Patties - Soyocak, Hilal; Proestos, Charalampos; Brennan, Charles; Wahab, Rizwan; Oz, Fatih; Turhan, Sadettin (Wiley, 2024)
This work aimed to determine the total anthocyanin and phenolic contents and antioxidant capacity of extracts of the black rice's cold, hot and ultrasonic-assisted extracts and their preservative effect on the storage quality of beef patties. The three extracts exhibited high anthocyanin, phenolic content and antioxidant capacity, and they were used in beef patties at five treatments (negative control without extract, positive control with 0.01% butylated hydroxytoluene (BHT), 7.5% cold extract, 7.5% hot extract and 7.5% ultrasound-assisted extract). Raw and cooked beef patties were tested at 0, 3, 6, 9 and 12 days of cold storage in aerobically packaged polyethylene containers regarding pH, oxidative stability, antioxidant capacity and microbial quality. While adding black rice extracts did not influence the proximate composition of raw samples (P > 0.05), it slowed down the pH and lipid oxidation during storage and provided pH and thiobarbituric acid reactive substances (TBARS) stability in all final products. The BHT and treatments with extract indicated a higher 2,2-diphenyl-1-picrylhydrazyl (DPPH) value than the negative control. Also, the incorporation of black rice extracts slightly retarded bacterial growth. These results suggest that the black rice extracts at 7.5% can be used effectively to protect beef patties from microbial spoilage and oxidation during cold storage for 12 days.
Proestos, Charalampos/0000-0002-3450-5969; Oz, Fatih/0000-0002-5300-7519; Wahab, Rizwan/0000-0003-0340-3844; Turhan, Sadettin/0000-0002-3510-4382; Brennan, Charles/0000-0003-2479-8478;
Keywords: Antioxidant Capacity; Bacteria Count; Beef Patty; Black Rice; Oxidative Stability